A multicentre study of primary breast diffuse large B‐cell lymphoma in the rituximab era. (27th January 2014) - Hosein, Peter J.; Maragulia, Jocelyn C.; Salzberg, Matthew P.; Press, Oliver W.; Habermann, Thomas M.; Vose, Julie M.; Bast, Martin; Advani, Ranjana H.; Tibshirani, Robert; Evens, Andrew M.; Islam, Nahida; Leonard, John P.; et al.
Summary Primary breast diffuse large B‐cell lymphoma (DLBCL) is a rare subtype of non‐Hodgkin lymphoma (NHL) with limited data on pathology and outcome. A multicentre retrospective study was undertaken to determine prognostic factors and the incidence of central nervous system (CNS) relapses. Data was retrospectively collected on patients from 8 US academic centres. Only patients with stage I/II disease (involvement of breast and localized lymph nodes) were included. Histologies apart from primary DLBCL were excluded. Between 1992 and 2012, 76 patients met the eligibility criteria. Most patients (86%) received chemotherapy, and 69% received immunochemotherapy with rituximab; 65% received radiation therapy and 9% received prophylactic CNS chemotherapy. After a median follow‐up of 4·5 years (range 0·6–20·6 years), the Kaplan–Meier estimated median progression‐free survival was 10·4 years (95% confidence interval [CI] 5·8–14·9 years), and the median overall survival was 14·6 years (95% CI 10·2–19 years). Twelve patients (16%) had CNS relapse. A low stage‐modified International Prognostic Index (IPI) was associated with longer overall survival. Rituximab use was not associated with a survival advantage. Primary breast DLBCL has a high rate of CNS relapse. The stage‐modified IPI score is associated with survival.